Guidelines Financial Support To Public Private Partnerships in Infrastructure - Planning Commission (Planning Commission, 2006)
This scheme aims at supporting infrastructure projects that are economically justified but fall short of financial viability. The lack of financial viability usually arises from long gestation periods and the inability to increase user charges to commercial levels. Infrastructure projects also involve externalities that are not adequately captured in direct financial returns the project sponsor. Through the provision a catalytic grant assistance of up to 20% of the capital costs, several projects may Become bankable and help mobilise the which needed private capital and efficiencies.
Planning Commission Government of India
Planning Commission Government of India